2015
DOI: 10.14485/hbpr.2.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Optimism and Cardiovascular Health: Multi-Ethnic Study of Atherosclerosis (MESA)

Abstract: Objectives We examined the cross-sectional association between optimism and cardiovascular health (CVH). Methods We used data collected from adults aged 52–84 who participated in the Multi-Ethnic Study of Atherosclerosis (MESA) (n=5,134) during the first follow-up visit (2002–2004). Multinomial logistic regression was used to examine associations of optimism with ideal and intermediate CVH (with reference being poor CVH), after adjusting for socio-demographic factors and psychological ill-being. Results Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 53 publications
5
40
0
1
Order By: Relevance
“…Importantly, although optimism is shaped by social structural factors (e.g., SES) and is approximately 25% heritable, 4,5 randomized trials suggest optimism can be modified using approaches including cognitive-behavioral therapy, as well as less intensive classroom-style activities and brief paper and pencil exercises—some of which are inexpensive and accessible. 69 Optimism has been associated with healthier behaviors (e.g., diet, medication adherence), 1013 improved biologic functioning (e.g., less inflammation, healthier antioxidant levels), 1416 and reduced risk of chronic diseases 17,18 and mortality. 19,20 Yet, it remains largely unknown whether any prolonged longevity is accompanied by overarching health.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, although optimism is shaped by social structural factors (e.g., SES) and is approximately 25% heritable, 4,5 randomized trials suggest optimism can be modified using approaches including cognitive-behavioral therapy, as well as less intensive classroom-style activities and brief paper and pencil exercises—some of which are inexpensive and accessible. 69 Optimism has been associated with healthier behaviors (e.g., diet, medication adherence), 1013 improved biologic functioning (e.g., less inflammation, healthier antioxidant levels), 1416 and reduced risk of chronic diseases 17,18 and mortality. 19,20 Yet, it remains largely unknown whether any prolonged longevity is accompanied by overarching health.…”
Section: Introductionmentioning
confidence: 99%
“…One previous study reported associations between optimism and ideal cardiovascular health, but the cross-sectional design limited conclusions about the direction of the relationship. 26 However, the current study is the only one that investigates how psychosocial factors in older adulthood might contribute to achieving and maintaining FCH over time.…”
Section: Discussionmentioning
confidence: 99%
“…Higher levels of optimism have been associated with lower inflammatory cytokine levels and C-reactive protein [147], and lower inflammatory response to experimental stress [148]. However, optimism is an asset highly associated with socioeconomic advantage [149] and healthy lifestyle habits [5,150,151]. Optimism also has complex ties to sleep; optimism improves sleep, yet poor sleep appears to promote pessimism [152].…”
Section: Positive Emotions and States: Neglected Discussionmentioning
confidence: 99%
“…We highlight the emerging research on positive emotions (rather than exclusively negative emotions typical of the study of depression and/or anxiety) and their associations with immune function, stress physiology and non-communicable disease (NCD) risk [4,5,6]. Further, we explore the rapidly-evolving and no less interconnected realm of nutrition and mental health [7].…”
Section: Roadmap To the Current Reviewmentioning
confidence: 99%